Soil health for the semi-arid west: a nexus of agricultural soil management and ecosystem services - Trimarco, Tad, author; Ippolito, James A., advisor; Wardle, Erik, committee member; Harmel, Robert Daren, committee member; Seidl, Andrew, committee member (Colorado State University. Libraries, 2025)
Our agricultural systems face increasing pressure to simultaneously intensify their operations while reducing the unintended environmental consequences of production. In the semi-arid western US, the most pressing concerns for the continued sustainability of agriculture include: 1) maintaining a healthy topsoil for reliable productivity, 2) mitigation of water pollution from agricultural runoff, and 3) ensuring profitability of farms to maintain or improve quality of life for producers. These concerns have been studied individually but have rarely been connected empirically. Even fewer studies have attempted a holistic, systems-wide approach to soil health management in semi-arid regions, where irrigation is critical to maintaining robust production. To address this gap in the current research, I performed a series of soil health assessments across five sites in Colorado, USA using the Soil Management Assessment Framework and connected these soil health measurements to indicators of runoff water quality, water conservation, or economic welfare. These sites were a combination of small and medium-sized farms operated by either research staff at research farms or by small farmers on private land. The objective of the research was to monitor soil health on sites implementing Best Management Practices (BMPs) for soil or water conservation and evaluate the ecosystem service impact of these practices. Evaluated BMPs included: 1) conservation tillage under furrow irrigation, 2) transition from furrow irrigation to sprinkler irrigation, 3) installation of a vegetated filter strip, and 4) use of management-intensive grazing. The soil health impact of these BMP's was mixed; at some sites the long-term reduction in intensity of tillage had positive effects on soil health, whereas on others, the management of the field under deficit irrigation resulted in significant salinization of the soil subsurface. At the long-term conservation tillage site, empirical connections were established between edge of field water quality measurements and soil health indicators to identify that in these furrow-irrigated systems, improvement of both soil health and water quality can be achieved through improvement of infiltration and protection of soil aggregates. In irrigated systems, improvements of soil functioning to retain and store water is a critical ecosystem service. Furthermore, at this site, the economic impact and greenhouse gas mitigation potential of adopting conservation tillage with cost-sharing or carbon (C) offsetting and selling was assessed using a 12-year enterprise budget analysis. Results indicated that over the long-term, conservation tillage may be more profitable than conventional tillage, particularly when funding incentives are used to offset the early costs of adoption. Taken together, the results of these multiple studies indicate that management for water conservation may indeed improve soil health and economic outcomes, but continued monitoring of the soil system is necessary. This approach provides a blueprint for future systems-wide studies of conservation agriculture, which should consider hydrologic, agronomic, and socioeconomic impacts.
Keywords: conservation agriculture; soil health; water quality; soil carbon; agricultural economics; tillage